The Nottingham Expectation and Complication score following Surgery (NECS): an universal scale for surgical outcome audit and peer comparison. (4th March 2017) - Ingale, Harshal; Muquit, Samiul; Al-Helli, Othman; White, Barrie; Basu, Surajit
Abstract: Background: Consultant Outcomes Publication (COP) is an NHS England initiative for promoting improvements in quality of care. However, at present outcomes are commonly expressed as mortality rates which do not necessarily reflect the performance of surgeons. We developed the Nottingham Expectation and Complication score following Surgery (NECS) to determine the success of surgical treatment from both the clinical perspective and the practical expectations agreed between surgeons and patients during the consent process. Method: This was a pilot study to trial the use of the NECS score. It is a simple expression of overall outcome comprising three clinical domains: S – surgical outcome, T – surgical/technical complications and M – medical complications recorded by the treating clinician, and practical outcome determined by a joint clinical/patient assessment. 107 elective neurosurgical patients were included in this prospective study. 95 completed questionnaires were included. Results: 75% patients achieved the best possible treatment score (S3T3M4). Of the 25% of patients who did not achieve this ideal outcome, the most common cause was either medical deterioration 18%, or technical complications of surgery discussed during the consent process 17%, or both. Surgeons rated their outcomes as expectations exceeded in 2% of cases, met in 92%, partially met in 5% and failed in 1%. Patients rated their outcomes as expectations exceeded in 37%, met in 37%, partially met in 18%, and 5% reported that their expectations were not met or they were worse than before the operation. Bivariate correlation analysis (Pearson's r coefficient) between overall 'expectation score' of patients and surgeons showed moderate correlation with r  = .25 ( p  = .014). Conclusion: NECS score can be used as an indicator to assess technical performance and patient satisfaction. It provides a more balanced quality indicator of the surgical service delivery than COP. It also offers additional advantages for auditing/planning improving care and may serve as an appraisal/revalidation tool.